Estetika Tari Lango Dewi di Pura Beji Langon - Yulianti, Ni Luh Putu Erika; Trisnawati, Ida Ayu; Sulistyani, Sulistyani (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2023)
ABSTRACT Lango Dewi dance, inspired by a group of nymphs who came to Beji Langon to take Toya Amertha. Beji Langon, also known as Pancoran Dedari, is located in Kapal Village, Mengwi, Badung. Beji Langon Temple is a temple that serves as the location of Ida Bhatara's purification which is located at the Kahyangan Temple in the Three Traditional Ship Villages, namely Pura Desa, Pura Puseh and Pura Dalem. The manifestation of Ida Sang Hyang Widhi who is worshiped at Beji Langon Temple is Dewi Gangga, as the Goddess of water who is in charge of purifying this universe. Goddess Gangga is worshiped at Beji Langon Temple because at this temple a statue of the goddess was found sitting in the middle of the main pool of Beji Langon Temple. Thus, this Beji temple functions as a place of purification and cleansing on a scale and no basis). Beji Langon Temple is one of the relics of an old site in Badung that has recorded traces of water civilization in the Badung area. On this occasion the researcher took the MBKM policy for the Research or Research program with the object of research being the Lango Dewi Dance. The purpose of this study was to analyze the aesthetics contained in the Lango Dewi Dance. The method used in this research is qualitative method. The research method includes observation, interviews, literature study, and documentation. The function and meaning can be seen, the primary and secondary functions of the Lango Dewi Dance and the meaning to society and the Lango Dewi Dance studio. Keywords: Lango Dewi, Beji Langon Temple, Form, Aesthetics, Meaning and Function.